Occurrence and Phylogenetic Analysis of DWV in Stingless Bee (Apidae sp.) in China: A Case Report - Zhang, Lina; Deng, Yanchun; Zhao, Hongxia; Zhang, Ming; Hou, Chunsheng (Frontiers in Insect Science, 2021)
Honey bees play a vital role in providing pollination services for agricultural crops and wild flowering plants. However, the spillover risk of their pathogens to other pollinators or wild insects is becoming a cause for concern. There is some evidence that stingless bees can carry honey bee viruses, but little is known about the presence of honey bee viruses in stingless bees in China. Here, we investigate the occurrence of major honey bee pathogens including bacteria, fungi, and viruses in stingless bees (Apidae: sp.). Our results show that the stingless bees (Apidae: sp.) were mainly infected with DWV-A, but no DWV-B and DWV-C. Phylogenetic analysis on fragments of lp, RdRp, and VP3 of DWV-A indicated that genetic variation in VP3 might an important indicator for host-specific viruses, but it requires further study. Our results indicated that DWV-A is not only the major strain of virus currently circulating in managed bee colonies in China and globally, but in stingless bee species as a whole.